Efficacy of arthroscopically placed pain catheter adjacent to the suprascapular nerve (continuous arthroscopically assisted suprascapular nerve block) following arthroscopic rotator-cuff repair - Yamakado, Kotaro (Dove Medical Press, 2014)
BACKGROUND: Rotator-cuff surgery is well recognized to be a painful procedure. OBJECTIVES: The purpose of this study was to examine the effectiveness of an arthroscopically placed perineural catheter at the scapular notch to provide a continuous block of the suprascapular nerve (continuous arthroscopically assisted suprascapular nerve block [ca-SSNB]) following arthroscopic rotator-cuff repair (ARCR). MATERIALS AND METHODS: This level II, prospective, randomized, controlled trial without postoperative blinding included 40 patients, who had a 48-hour pain pump, with 0.2% ropivacaine infusion and a continuous rate of 3 mL/hour, placed via an arthroscopically placed catheter following ARCR with arthroscopic release of the superior transverse ligament: 21 patients had a ca-SSNB, and 19 patients had a continuous subacromial bursal block (SAB). The visual analog scale (at 6 hours and on the first, second, and third postoperative days) and the total number of additional pain-reduction attempts during the 3 postoperative days were calculated. RESULTS: The respective visual analog scale scores (mm) obtained from the ca-SSNB and SAB groups were 62.4 and 67.6 (P=0.73) before surgery, 9.1 and 19.4 (P=0.12) at 6 hours after surgery, 24.4 and 44.6 (P=0.019) on the first postoperative day, 19.4 and 40.4 (P=0.0060) on the second postoperative day, and 18.5 and 27.8 (P=0.21) on the third postoperative day. Total additional pain-reduction attempts recorded for the ca-SSNB and SAB groups during the 3 postoperative days were 0.3 times and 1.2 times (P=0.0020), respectively. CONCLUSION: ca-SSNB was highly effective in controlling postoperative pain after ARCR.